2020
DOI: 10.21203/rs.3.rs-41260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developments in asthma incidence and prevalence in Alberta between 1995 and 2015

Abstract: Background: Asthma is a chronic respiratory disease characterized by reversible bronchoconstriction and airway inflammation. According to Statistics Canada in 2014, 8.1% of Canadians aged 12 and older reported having asthma diagnosed by a health care professional. Therefore, in 2014 there were an estimated 274,661 persons with asthma in Alberta. Most epidemiological studies estimate prevalence and incidence using survey-based data, which has limitations. The Ontario Asthma Surveillance Information System (OASI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…While there are standard recommendations and guidelines for the diagnosis and treatment of asthma, patients living with this disease often experience poor health-related quality of life [3] and continue to experience exacerbations [4]. Apart from the increasing air pollution, rapid urbanization, and a growing trend in marijuana and vaping, particularly among the adolescents [5][6][7][8], poor patient adherence to asthma medications is a major contributing factor to these outcomes [9][10][11][12]. Despite efforts to change this narrative through patient and physician education [13][14][15], it is well reported that adherence to treatment in asthma is varied, with rates of <50% in children [16] and 30-70% in adults [1,17].…”
Section: Word Count: 1512mentioning
confidence: 99%
“…While there are standard recommendations and guidelines for the diagnosis and treatment of asthma, patients living with this disease often experience poor health-related quality of life [3] and continue to experience exacerbations [4]. Apart from the increasing air pollution, rapid urbanization, and a growing trend in marijuana and vaping, particularly among the adolescents [5][6][7][8], poor patient adherence to asthma medications is a major contributing factor to these outcomes [9][10][11][12]. Despite efforts to change this narrative through patient and physician education [13][14][15], it is well reported that adherence to treatment in asthma is varied, with rates of <50% in children [16] and 30-70% in adults [1,17].…”
Section: Word Count: 1512mentioning
confidence: 99%
“…As of 2018, approximately 12% of Canadians (i.e., 3 million people) and 12% of Albertans have been diagnosed with asthma [3,4]. Asthma prevalence is increasing in Alberta [5], where the asthma incidence rate was highest in children aged 1 to 14 [6]. Children are more susceptible to asthma onset, likely a result of a less developed immune system, smaller lung passages, increased exposure to outdoor pollutants, and increased pollutant inhalation per body weight [7].…”
Section: Introductionmentioning
confidence: 99%